2014
DOI: 10.5334/jbr-btr.1326
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Plantar Fascia in Asymptomatic Subjects

Abstract: Plantar fasciitis is a low-grade inflammation of the plantar fascia and perifascial tissues. It is a common cause of heel pain and usually affects middle-aged women, as well as younger, predominantly male, runners (1). The condition is likely related to repeated strain, leading to microtears and inflammation. Imaging is commonly used to confirm the diagnosis, and exclude other causes of posterior heel pain (2).Although MR imaging may be used to diagnose plantar fasciitis, many authors suggest ultrasound is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
4
13
3
Order By: Relevance
“…When comparing the plantar fascia thickness between healthy males and females, no significant difference in plantar fascia thickness was found collectively or at any MTP joint extension position (Table 2). Previous studies have also found no difference in plantar fascia thickness between males and females, 10,14,24,38 which is in contrast to other studies that identified males as having thicker plantar fasciae than females. 2,14,34 Huerta and Garcia found that males had increased plantar fascia thickness when measured 1 cm proximal to the plantar fascia insertion, whereas they found no difference among males and females when the thickness was measured at the insertion (ie, anterior border of the calcaneus where the plantar fascia just leaves the calcaneal tuberosity) or 1 or 2 cm distal to the insertion.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…When comparing the plantar fascia thickness between healthy males and females, no significant difference in plantar fascia thickness was found collectively or at any MTP joint extension position (Table 2). Previous studies have also found no difference in plantar fascia thickness between males and females, 10,14,24,38 which is in contrast to other studies that identified males as having thicker plantar fasciae than females. 2,14,34 Huerta and Garcia found that males had increased plantar fascia thickness when measured 1 cm proximal to the plantar fascia insertion, whereas they found no difference among males and females when the thickness was measured at the insertion (ie, anterior border of the calcaneus where the plantar fascia just leaves the calcaneal tuberosity) or 1 or 2 cm distal to the insertion.…”
Section: Discussioncontrasting
confidence: 88%
“…2,3,21,37,38 However, plantar fascia thickness norms for men and women have varied in the literature. Some studies have found no differences in plantar fascia thickness between men and women, 10,14,24,38 whereas other studies have identified men as having increased plantar fascia thickness compared with women. 2,14,34 Gender and its inconsistent relationship in the literature pertaining to plantar fascia thickness is still unclear.…”
mentioning
confidence: 99%
“…We believe that the few asymmetric values would be partly related to a measurement error since the difference did not exceed 0.20 mm. This symmetry was also found by Gadalla et al [12] This symmetry is preserved even if the thickness of the PF decreases progressively away distally from the insertion. According to the walking activity, the thickness of the PF increased as a function of the daily distance traveled.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the BMI also participated as a factor favoring the thickening of PF. On the other hand, the thickness of the PF at the right and at the left side did not vary according to the gender of the participants as found by Gadalla et al [12] while Pascual Huerta and Alarcón García found a variation in the thickness of the PF measured at its insertion and at 1 cm distally according to gender and that he considered related to the difference of certain fibers that would be thicker in men than in women, and he concluded that the thickness of PF in men exceeds 0.42 mm that of women. [4] The thickness of the PF at right and left was symmetrical in 90.3%.…”
Section: Discussionsupporting
confidence: 59%
“…The former involves connection via connective tissue whereas the latter details patterns within the trabeculae of the calcaneus, which are aligned in the direction of the fascicles from the AT to the PF. Moreover, there is conflicting evidence of correlations existing between traits such as age, sex and body size against the thicknesses and CSAs of the AT and PF [17][18][19][20][21][22] . Conclusively, if there are significant correlations found between the thicknesses or CSAs of the AT and PF, it will provide additional evidence on a morphological relationship between the two structures, furthermore implying a functional one according to the concept of 'structure and function' .…”
mentioning
confidence: 99%